Anxiety in students with intellectual disabilities: the influence of staff-perceived social acceptance and rejection in the classroom - Hofmann, Verena (Frontiers in Education, 2023)
Students with intellectual disabilities often exhibit increased anxiety levels, which can be associated with additional limitations and severe emotional distress. This study investigated the role of social acceptance, social rejection, and general functioning in predicting anxiety. Using data on 1,125 students in 179 special needs classrooms that was collected at the beginning and end of one school year, multilevel models were used to predict whether future anxiety was associated with prior staff-perceived social acceptance or rejection by classmates, and with general functioning. We found that greater staff-perceived social acceptance was related to a decrease in anxiety over the school year, however, no effect was found for rejection. Further, there was no moderating effect of students’ general functioning. Positive peer relationships in the classroom appear to contribute to lower anxiety, while negative relationships do not further worsen anxiety. Implications for special needs schools are discussed.